2016
DOI: 10.1371/journal.pone.0146493
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Calmodulin-Binding Domains of Fas Death Receptor

Abstract: The extrinsic apoptotic pathway is initiated by binding of a Fas ligand to the ectodomain of the surface death receptor Fas protein. Subsequently, the intracellular death domain of Fas (FasDD) and that of the Fas-associated protein (FADD) interact to form the core of the death-inducing signaling complex (DISC), a crucial step for activation of caspases that induce cell death. Previous studies have shown that calmodulin (CaM) is recruited into the DISC in cholangiocarcinoma cells and specifically interacts with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…The scheme showing the disordered and ordered protein structures has been reprinted from reference [16] (Figure 1, Copyright (2018), with permission from Elsevier). In the panel "Tools to study chaperone structural dynamics", the NMR spectrum has been modified from reference [17], the Molecular Dynamics Simulations image has been reprinted from reference [18], the Cryo-EM maps have been reprinted from reference [19].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…The scheme showing the disordered and ordered protein structures has been reprinted from reference [16] (Figure 1, Copyright (2018), with permission from Elsevier). In the panel "Tools to study chaperone structural dynamics", the NMR spectrum has been modified from reference [17], the Molecular Dynamics Simulations image has been reprinted from reference [18], the Cryo-EM maps have been reprinted from reference [19].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Of note, it has been reported that the CD95‐mediated Ca 2+ response might also affect the DD‐dependent interactome. For instance, calmodulin docks onto the CD95‐DD in a Ca 2+ ‐dependent manner and prevents FADD recruitment .…”
Section: Unknown Factors In Disc Formationmentioning
confidence: 99%